Is Nipple-Sparing Mastectomy Indicated after Previous Breast Surgery? A Series of 387 Institutional Cases. Issue 1 (July 2021) - Vicini, Elisa; De Lorenzi, Francesca; Invento, Alessandra; Corso, Giovanni; Radice, Davide; Bozzo, Samantha; Kahler Ribeiro Fontana, Sabrina; Caldarella, Pietro; Veronesi, Paolo; Galimberti, Viviana
Abstract : Background: Previous breast surgery does not represent an absolute contraindication for nipple-sparing mastectomy, although it may negatively interfere with surgical outcomes. The aim of the authors' study was to confirm the feasibility of nipple-sparing mastectomy after previous breast surgery, focusing on skin incisions and risk factors, complications, and oncologic outcomes. Methods: The authors retrospectively identified 368 patients who underwent 387 nipple-sparing mastectomies and reconstruction after previous surgery (quadrantectomy, breast resection, augmentation and reduction mammaplasty, mastopexy) at the European Institute of Oncology from January of 2003 to November of 2017. Patterns of skin incisions (i.e., radial, hemiperiareolar, periareolar, vertical pattern, inframammary fold, Wise-pattern, and round-block) for primary surgery and for mastectomy, type of reconstruction, and radiotherapy have been recorded. The authors collected data regarding early and late complications and further operations (implant change, fat grafting) performed within 2 years to improve cosmetic outcomes. Oncologic follow-up has been reported for in-breast recurrences. Results: Complete and partial nipple-areola complex necrosis occurred, respectively, in 2.8 percent and in 5.4 percent of cases. The authors recorded 5.4 percent failures resulting in implant removal. The analysis of risk factors for complications or for the need for further operations showed no significant association with skin incision for first surgery and mastectomy, use of the same skin incision, previous radiotherapy, or type of primary surgery. Five-year overall survival and disease-free survival were 99.1 and 93.8 percent, respectively. No nipple recurrence was recorded. Conclusions: The authors' results confirm that nipple-sparing mastectomy can be a safe surgical procedure after previous breast surgery. Surgical planning should be tailored to each patient. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.